Penanaman Budaya Belajar Bagi Santri Bagi Pondok Pesantren Nurul Muhajirin Sukatani-Banyuasin - Siti Zailiah (Pusat Riset dan Inovasi Nasional, 2023)
This article is entitled Planting a Learning Culture for Santri for Nurul Muhajirin Sukatani-Banyuasin Islamic Boarding School, with the aim of how the process of cultivating a student learning culture at Nurul Muhajirin Sukatani Islamic Boarding School. The type of research used is qualitative with a descriptive approach. Data collection techniques used through observation, interviews, and documentation. Data analysis techniques start from collecting data, presenting data, and drawing conclusions. While the technique of checking the validity of data is by data triangulation techniques. The results obtained that the cultivation of a learning culture for Santri for Nurul Muhajirin Islamic Boarding School has been carried out well, including making a schedule of activities, time and place of study, which is in accordance with the needs of education at Ponpes Nurul Muhajirin, Ponpes has also provided education to get used to reading and taking notes for Ponpes students, Ponpes also makes schedules and rules for students to repeat learning materials when returning home from formal learning classes, then concentration in learning is also a serious concern for Ponpes in order to get maximum results, and has also instilled the value that the importance of carrying out or doing the tasks given by the ustad / ustazah.